Micro UAV Swarm for industrial applications in indoor environment: A systematic literature review - Shrutarv Awasthi; Miguel Fernandez-Cortizas; Christopher Reining; Pedro Arias-Perez; Marco Andres Luna; David Perez-Saura; Moritz Roidl; Nils Gramse; Patrick Klokowski; Pascual Campoy (Logistics Research, 2023)
This contribution provides a systematic literature review of micro aerial vehicle (MAV) swarms for indoor industrial applications. First, an initial list of 1997 publications that complies with predefined inclusion criteria was surveyed by reviewers. Next, 185 publications that comply with the Selection Process were analyzed based on localization, control, guidance system, safety and security, MAV charging, communication, artificial intelligence, and applications. The analyzed researches could possibly be deployed in the industrial application of production, logistics and supply chain or transferable into this field. The publications encompassed within this study can be classified under Technology Readiness Level (TRL) 4. Some works do strive to offer solutions tailored to industrial tasks, the validation of their findings predominantly occurs through simulations or controlled laboratory environments. The findings provide an overview of the state-of-the-art specifications, the technologies used by MAVs, trends and outline a future road map for further research from a practitioner's perspective.
Keywords: 650; MAV swarm; indoor; logistic; supply chain